BRAND IMAGE: UPAYA MEMASARKAN PENDIDIKAN BAGI LEMBAGA YANG KURANG MAMPU BERSAING - FAJRI DWIYAMA (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract. The focus of discussion in this paper is to provide an overview of efforts to market education to the community through the creation of a positive brand image for educational institutions. The background is government policies that give authority to educational institutions in managing their respective educational institutions so as to open the door to competition between educational institutions. Seeing the condition of competition that tends to be less healthy, encourages the writer to explain the concepts that can help educational institutions to be able to recognize the efforts made in marketing education, especially in terms of creating brand image. This becomes very important to be understood by the management of educational institutions, considering the brand image is the embodiment of an educational institution in the minds of consumers (students, students, students, and society) in assessing and dropping their choices to contribute to the chosen educational institution.